Experimental study on the effects of fine sand addition on differentially compacted pervious concrete. (30th August 2015) - Bonicelli, Alessandra; Giustozzi, Filippo; Crispino, Maurizio
Highlights: Sand addition to mixes produces a significant increase in mechanical properties. Porosity and drainability were reduced while increasing the sand content. The effect of sand addition was influenced by the water content of the mixes. Proper energy of compaction produced satisfactory drainability and strength. An analytical model for material properties was implemented based on lab results. Abstract: Pervious concrete provides a sound solution for managing storm waters in built environments where the water runoff as well as the natural recharge of the groundwater are important issues. The use of pervious concrete is also commonly related to other environmental benefits such as the Urban Heat Island reduction, traffic noise absorption, and pollutant filtering. Despite the broad capabilities, comprehensive standards are still limited and many issues have not yet been completely fixed. For example, compaction is often underestimated and one of the common compaction effort is provided by hand-rolling; however, different compaction energies, techniques, or timing can significantly affect mechanical and functional properties of the material. Performance can be furthermore improved by adding a small amount of fine sand, as suggested by many; sand can lead towards better raveling and skid resistance, also improving the maximum flexural strength. On the other hand, too much sand and improper compaction energy may lead to an excessively low void content and reduced drainability features. Compaction and sand addition should be therefore analyzed more in details. The present research aimed at (1) evaluating the effect of differential levels of compaction energy and (2) analyzing the influence of fine sand addition into several pervious concrete mixtures. Results suggested that adding small amounts of fine sand (around 5% of the total aggregate weight) to pervious concrete mixtures provided better mechanical and surface properties, and a consequent reduction of drainability. However, the correct balance of mechanical and hydrological properties can be achieved due to both accurate mix-design and proper compaction plan.